PEMULIHAN KEKUATAN TARIK BELAH BETON DENGAN VARIASI DURASI PERAWATAN PASCA BAKAR - Sutapa, A.A. Gede; Oka Suputra, I G.N.; Mataram, Karnata (Jurnal Ilmiah Teknik Sipil, 2012)
Research on the post-fire concrete immersed in the water expects that its strength can be recovered with a simple and inexpensive ways. By reactivating hydration process, the concrete’s strength can be recovered regardless of the age of the post-fire concrete. The time needed to improve the post-fire concrete strength depends on the immersed time duration in the water. This research is carried out to determine the relationship between the immersed time duration in the water and the level of concrete strength recovery. The average of split tensile strength of concrete post-fire at a temperature of +800 °C is of 31.707% or it is decreased by 68,393%. The splitting tensile strength of post-fire concrete after being immerse in the water during 7, 14 and 28 days are of 64,808%, 67,908% and 56,494% of standard concrete respectively, or decreased by 35,192%, 32.092% and 43.506% respectively. Soaking for 14 days provides the level of recovery of splitting tensile strength of concrete post-fire at its optimum. Soaking longer tends to reduce the recovery rate of tensile strength of concrete post-fire.
Keywords: duration of immersion, the recovery of splitting tensile strength of concrete, concrete post-fire